2012
DOI: 10.2176/nmc.52.521
|View full text |Cite
|
Sign up to set email alerts
|

Watertight Dural Closure Constructed With DuraSeal<sup>TM</sup> for Bypass Surgery

Abstract: Superficial temporal artery-middle cerebral artery (STA-MCA) anastomosis is a common procedure for the treatment of cerebral ischemia and is useful for cerebral aneurysms and tumors. The STA has to pass through the dura and the dura cannot be sutured tightly around the STA to prevent vessel narrowing, so subcutaneous cerebrospinal fluid (CSF) collection is common. This study analyzed the feasibility of using a synthetic dural sealant in the STA-MCA anastomosis to establish watertight closure. Twenty-four patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…They found that easy and effective sealing of the field was achieved by the dura seal. [ 21 ] Only 2/24 patients developed subcutaneous CSF fistula later on. The usage of the dura seal gave no negative effects on the patency of the anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…They found that easy and effective sealing of the field was achieved by the dura seal. [ 21 ] Only 2/24 patients developed subcutaneous CSF fistula later on. The usage of the dura seal gave no negative effects on the patency of the anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Duraseal® (Confluent Surgical, Inc., Waltham, MA) is an FDAapproved surgical sealant that is generally used to prevent cerebrospinal fluid leaks in cranial and spinal surgery as well as for improved anastomotic safety in cardiovascular surgery (Jeon et al, 2017;Nishimura, Kimura, & Morita, 2012;Osbun et al, 2012;Pereira, Grandidge, Nowak, & Cudlip, 2017;Strong et al, 2017).…”
Section: Duraseal®mentioning
confidence: 99%
“…In a study reported by Nishimura et al in 2012, DuraSeal was analyzed to test its feasibility for use in superficial temporal artery-middle cerebral artery anastomosis, a common procedure for the treatment of cerebral ischemia, cerebral aneurysms and tumors. In a cohort of 42 patients, DuraSeal obtained a water-tight dural closure easily and safely, even in bypass surgery [35]. …”
Section: Sealantsmentioning
confidence: 99%